Interpretation of Vyacheslav Ivanov’s Symbols in the Collection of Poems Let it Be So by Yury Verkhovsky - Liubov V. Mashtakova (Studia Litterarum)
This article examines the last collection of poetry by Yury Verkhovsky entitled Let it Be So published in his lifetime (Sverdlovsk, OGIZ Sverdgiz, 1943). This collection of poems, apart from its overall pro-military and patriotic pathos, covertly continues the tradition of friendship epistles of Verkhovsky and Ivanov. Bearing on the aesthetic discoveries of Symbolism in the years between the 1900s and the 1910s, the collection introduces the typically symbolist temporal and spatial model that, however, relates itself to the current historical situation. The article specifically focuses on the mythopoetic component of the so-called “Ural text”, organically included in the poetics of Verkhovsky in the 1940s as it extends the field of symbols and allusions shared by Verkhovsky and Ivanov. The article also explores the concept of memory in Ivanov’s and Verkhovsky’s work and its development from the earlier poems to the wartime poems (Roman Diary, 1944) by Ivanov and Budet tak (Let it Be So) by Verkhovsky. The latter interprets general notions about the world cultural memory according to the logic of wartime: the expected victory of the Soviet army in the World War II becomes the central event of history, central target of the spiritual forces of the people — represented as the collective team where everyone is responsible and must be “on duty.” By contrast, In Ivanov’s Roman Diary, the events of the personal life of the soul dominate over the events of the war as they enter the “great time” of human history. Thus, in the 1940s, on the example of two poetic testimonies, we witness the main divergence of two Symbolist poets.